Classification of rhinoplasties performed in an otorhinolaryngology referral center in Brazil - Nunes, Flávio Barbosa; Crosara, Paulo Fernando Tormin Borges; de Oliveira, Isamara Simas; Evangelista, Leandro Farias; Rodrigues, Danilo Santana; Becker, Helena Maria Gonçalves; Guimarães, Roberto Eustáquio Santos (Brazilian journal of otorhinolaryngology, 2014)
Facial plastic and reconstructive surgery involves the use of surgical procedures to achieve esthetic and functional improvement. It can be used for traumatic, congenital, or developmental injuries. Medicine, with an emphasis on facial plastic surgery, has made progress in several areas, including rhinoplasty, providing good long-term results and higher patient satisfaction. To evaluate cases of rhinoplasty and its subtypes in a referral center, and to understand the relevance of teaching rhinoplasty techniques in a service of otolaryngology residency. A retrospective study that assessed 325 rhinoplasties performed by third-year medical residents under the supervision of chief residents in charge of the Service of Facial Plastic Surgery in this hospital was conducted from January of 2003 to August of 2012. The Service Protocol included the following subtypes: functional, esthetic, post-traumatic, revision, and reconstructive rhinoseptoplasty. Of the rhinoplasties performed 184 (56.21%) were functional, 59 (18.15%) were post-traumatic, 27 were (8.30%) esthetic, 15 were (4.61%) reconstructive, and 40 (12.30%) were revision procedures. Functional rhinoseptoplasties were the most prevalent type, which highlights the relevance of teaching surgical techniques, not only for septoplasty, but also the inclusion of rhinoplasty techniques in teaching centers. A cirurgia estética e reconstrutora têm por objetivo a utilização de procedimentos cirúrgicos para alcançar melhora estética e funcional. Pode ser utilizada para lesões traumáticas, congênitas ou de desenvolvimento. A Medicina, com ênfase na plástica facial, obteve avanços nas mais diversas áreas, inclusive na rinoplastia, permitindo bons resultados a longo prazo e maior satisfação dos pacientes. Avaliar a casuística do setor de rinoplastia e suas subdivisões em um centro de referência. Compreender a relevância do ensino das técnicas de rinoplastia em um serviço de residência médica de otorrinolaringologia. Estudo retrospectivo onde foram analisados 325 rinoplastias, realizadas por médicos residentes do terceiro ano com supervisão dos preceptores responsáveis pelo serviço de Cirurgia Plástica da Face desse hospital, no período de janeiro de 2003 a agosto de 2012. O protocolo do serviço foi preenchido com enfoque nas seguintes subdivisões: rinosseptoplastia funcional, estética, pós-traumática, revisional e reconstrutora. Das rinoplastias realizadas, 184 (56,21%) foram funcionais, 59 (18,15%) pós-traumáticas, 27 (8,30%) estéticas, 15 (4,61%) reconstrutoras e 40 (12,30%) revisionais. As rinosseptoplastias funcionais foram as mais prevalentes, o que mostra a importância do ensino, não somente das técnicas de septoplastias, mas também, da inclusão do aprendizado de técnicas de rinoplastias em centros de ensino.